2022
DOI: 10.1136/ijgc-2021-002528
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adjuvant radiation for cervix cancer: reflections on the evidence and a peep into the future

Abstract: Early stage cervical cancer, stages IB1–2 and IIA1, can be treated with (chemo)radiation and brachytherapy or radical hysterectomy with or without further adjuvant (chemo)radiation. In a carefully selected cohort for surgery, traditionally a small proportion of patients would need adjuvant (chemo)radiation so that the therapeutic ratio is maximized. However, advances in radiation technology, specifically intensity modulated radiotherapy, have led to a reduction in treatment related adverse events. Also, recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…For future studies, implementation of these techniques should be considered, seeking to improve pelvic control and thereby disease free survival, with a lower threshold (8-10% risk of pelvic relapse). 36 Further Points of Consideration The study of Sedlis et al demonstrated a reduction in risk of recurrence after radiotherapy, but not in overall survival. One potential reason is that the sample size might have been too small as this study was planned to have 80% power to detect risk reductions of 46% or greater in overall survival; however, patients with radiotherapy had only a 30% reduction in the risk of mortality and significance was not reached.…”
Section: Advances In Radiotherapy Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…For future studies, implementation of these techniques should be considered, seeking to improve pelvic control and thereby disease free survival, with a lower threshold (8-10% risk of pelvic relapse). 36 Further Points of Consideration The study of Sedlis et al demonstrated a reduction in risk of recurrence after radiotherapy, but not in overall survival. One potential reason is that the sample size might have been too small as this study was planned to have 80% power to detect risk reductions of 46% or greater in overall survival; however, patients with radiotherapy had only a 30% reduction in the risk of mortality and significance was not reached.…”
Section: Advances In Radiotherapy Techniquesmentioning
confidence: 99%
“…Further control in the pelvis, specifically in the vagina, may be achieved by using additional vaginal brachytherapy. 36 Bronsart et al 44 examined the role of adjuvant brachytherapy alone as an alternative to external beam radiation therapy in 40 patients. This treatment was indicated when tumor size was ≥2 cm and/or in the presence of lymphovascular space invasion.…”
Section: Considerations For Adjuvant Therapy In the Intermediate Risk...mentioning
confidence: 99%
See 2 more Smart Citations